Progressive Pulmonary Artery Dilatation is Associated with Type B Aortic Dissection in Patients with Marfan Syndrome - Brouwer, Christel (J Clin Med, 2019)
Objective: Marfan syndrome (MFS) is a connective tissue disorder associated with severe cardiovascular morbidity and mortality. It is unknown if aorta complications in MFS are associated with progressive pulmonary artery (PA) dilatation. Methods: We measured the PA diameter on routine magnetic resonance imaging in a population of MFS patients seen in our specialised centre with follow up of diameters as well as the outcome. Results: PA dilatation was defined as an increase in diameter of 2 mm or more, and 71 patients (44%) of our total cohort (n = 162) met this criterion; mean follow up between two scans was 8.6 years (standard deviation (SD) ± 2.7 years). Furthermore, 28 patients suffered from dissections, of which 14 had a type A dissection, 10 had a type B dissection, and 4 patients suffered from both. Of those who suffered from dissection, 64% (18 out of 28) had a dilatation of the PA, versus 39% (53 out of 134) in the patient group without a dissection (p < 0.05). There was a significant association between type B dissection and descending aorta diameter (OR 1.14; 95% CI 1.05–1.24 p < 0.01) and PA dilatation (OR 1.69; 95% CI 1.03–2.77 p = 0.04). In the multivariable analysis the final model for type B dissection, only systolic blood pressure (OR 1.06; 95% CI 1.01–1.11 p = 0.02) and PA dilatation were statistically significant (OR 1.85; 95% CI 1.10–3.12 p = 0.02) while descending aorta diameter was not. Conclusions: We report an association between progressive PA dilatation and type B dissection. Our findings encourage a renewed interest in PA dimensions in MFS.